Intake of iron and inhibitor are not related with anemia on the premarriage women - Prasetya Lestari; Yhona Paratmanitya; Siti Suliyah (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2018)
ABSTRACTBackground: One of the most frequent nutritional problems in Indonesia occurs is anemia due to iron deficiency. Forty-nine point one percent of women of childbearing age in Indonesia are anemic. Especially on groups of women of childbearing age are usually preparing themselves for married and will become a mother. Factors causing anemia among others insufficient iron intake and high absorption of Fe inhibitors (tannin, phytate, and oxalic acid). If the bride is married to status anemia will affect the birth of a less qualified generation.Objectives: To know the relationship between iron intake and Fe inhibitor with the incidence of anemia in the bride in the District Area Bantul Yogyakarta. type of research conducted was observational research using a cross sectional design. Number of study subjects as many as 68 respondents in the bride with the picking technique the sample uses quota sampling that meets the inclusion criteria and exclusion. Data collected were data of iron intake and Fe Inhibitors. The data were obtained by interview using SQFFQ. Statistic test used were Mann Whitney and Chi Square test with level of 90% confidence.Results: The incidence of anemia was 44.1%. Based on the results there was no significant difference between the mean intake of Fe anemia group with anemia not with (p = 0.387). There is no Tanin intake differences were significant between the anemia group and the not anemia with (p = 0.512). There was no difference in intake of Fitat was significant between the anemia group and the non-anemic with (p = 0.335). There was no significant difference in intake of  xalates between groups of anemia with no anemia with (p = 0.537). Based on Chi Square Test as well it was known that there is no significant relationship between intake of Fe and Fe inhibitor with anemia incidence (p> 0.05)Conclusions: There was no significant relationship between intake of Fe and Fe inhibitor with anemia incidenceKEYWORDS: anemia, iron intake, inhibitor Fe, prospective bride